Production of fluorescent antibody-labeling proteins in plants using a viral vector and the application in the detection of Acidovorax citrulli and Bamboo mosaic virus - Kuo, Song-Yi; Lin, Yuan-Chuen; Lai, Yi-Chin; Liao, Jia-Teh; Hsu, Yau-Heiu; Huang, Hsiou-Chen; Hu, Chung-Chi (PloS one, 2018)
Serological methods are relatively convenient and simple for the detection of pathogens for front-line workers. On-site visualization of the test results plays a pivotal role in the process. However, an efficient, universal labeling agent for antibodies is needed for the development of efficient serological detection tools. In this study, a Bamboo mosaic virus (BaMV)-based viral vector was employed to express recombinant proteins, collectively designated GfED, consisting of Staphylococcus aureus Protein A domain ED (SpaED) fused to either the N- or C-terminal of an improved green florescent protein (GFP) with or without the coat protein (CP) of BaMV, efficiently in Chenopodium quinoa. The GfED in crude leaf extracts could specifically attach to IgG molecules of rabbits and mice, effectively labeling IgG with GFP, emitting green light at 506 nm when excited at 450 nm using simple, handheld equipment. To demonstrate the applicability of GfED in serological assays, we have developed a fluorescent dot blot assay for the rapid detection of Acidovorax citrulli (Ac), a bacterial pathogen of cucurbits, and BaMV, a viral pathogen of bamboos. By using the crude extracts of inoculated C. quinoa leaves expressing GfED as an IgG-labeling agent, the pathogens were easily and quickly detected through uncomplicated operations using simple equipment, with results observable by the naked eye. Examination using fluorescent microscopy and transmission electron microscopy revealed that the GfED subunits may assemble into virus-like particles, which were further involved in the formation of aggregates of GfED-antibody-antigen complexes with the potential for fluorescence signal enhancement. The results suggested that plant-expressed GfED may serve as a promising alternative of IgG-labeling agent for current serological assays.